Ketidaktaatasasan Penerapan Ejaan Bahasa Indonesia (EBI) dalam Ragam Tulis - Ary Setyadi (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2021)
Based on the available data, it turns out that there are still many non-compliance with the application of Indonesian spelling (EBI) in the “written variety”, even though the existence of EBI which began with Indonesian Spelling Completed) or (EYD) has been in effect since 1972, and their existence is definitely a Guidebook. In connection with this fact, it is necessary to make an effort to prove it, because from several literature sources no one has specifically discussed it. The research was carried out in three strategic stages: (1) data collection stage, (2) data classification and analysis, and (3) report preparation. Data collection is done by listening to the technique of recording on a reading card, so that the data source focuses on the written source. The data classification and analysis stage is based on: 1) the use of the spelling writing system, and 2) the use of the punctuation writing system (in the text as a data source). Data analysis uses linguistic theory in the fields of: phonology, morphology, syntax, and semantics because the use of the spelling writing system and the use of the punctuation writing system refers to the text. The last stage is the preparation / preparation of reports. The results of the analysis show that the existence of EBI as a guide for writing is still far from what is expected, so it is necessary to realize that what is called: the use of a spelling writing system and the use of a punctuation writing system in written variety is binding, that is, it must be understood, obeyed, obeyed, and applied by the every Indonesian speaker.